High-intensity conditioning activity causes localized postactivation performance enhancement and nonlocalized performance reduction - Kolinger, D.; Stastny, P.; Pisz, A.; Krzysztofik, M.; Wilk, M.; Tsoukos, A.; Bogdanis, G. C. (The Journal of Strength and Conditioning Research, 2024)
This study aimed to examine whether a conditioning activity (CA) performed by the legs (barbell back squat) may cause postactivation performance enhancement (PAPE) on muscle groups other than leg extensors in isokinetic (eccentric [ECC] and concentric [CON]) and dynamic movement. Twelve male basketball players (age: 21.3 ± 3.2, body mass: 89.6 ± 14.1 kg, height: 187.4 ± 4.6 cm, and 1 repetition maximum (1RM) barbell back squat: 113 ± 21 kg) with previous resistance-training experience of at least 2 years, performed 3 sets of 3-4 repetitions of back-squats with submaximal load (60, 90, and 90% 1RM) as CA. Before and after the CA, they performed pretest and post-test in the form of countermovement jumps (CMJs) (localized) or explosive push-ups (EPUs) (nonlocalized) along with isokinetic flexion and extension at the knee (localized) or at the elbow (nonlocalized). The localized and nonlocalized protocols were divided into 2 days in a randomized order. The back squat as CA significantly increased peak torque (PT) (p < 0.05) in all CON and ECC muscle actions and average power per repetition (APPR) (p < 0.05) (all muscle actions except ECC flexion) of the localized isokinetic tests with large (>0.8) and medium (0.4-0.79) effect sizes and significantly decreased (p < 0.01) the PT and APPR (p < 0.01) of the nonlocalized isokinetic test in the ECC flexion. The CMJ and EPU tests showed no significant differences (p > 0.05) between premeasures and postmeasures of take-off height. The effect of PAPE seems to be specific to the muscles most involved in the CA, and the CA inhibits PT of subsequent muscle ECC contractions in muscles not involved in the CA.